Profil Nomophobia pada Siswa Sekolah Menengah Kejuruan di Kota Malang serta Implikasinya terhadap Layanan Bimbingan dan Konseling - Ramadiani, Novanda Nur Aidha (SENTRI: Jurnal Riset Ilmiah, 2025)
Nomophobia, or the fear and discomfort associated with being unable to use or access a smartphone, has become relevant to students as smartphones are increasingly integrated into communication, information access, and daily activities. This study aimed to describe nomophobia among twelfth-grade students at a vocational high school in Malang City based on overall level, age, gender, and its four dimensions.. This study employed a quantitative approach with a descriptive survey method. The population consisted of 196 twelfth-grade students, with 132 students selected as the research sample based on predetermined criteria. Data were collected using the Nomophobia Questionnaire (NMP-Q), which measures four dimensions: not being able to communicate, losing connectedness, not being able to access information, and giving up convenience. Data were analyzed using descriptive statistics based on logit scores, frequencies, percentages, and Mean Item Scores. The findings showed that 60 students (45.45%) were categorized as having moderate nomophobia, 47 students (35.61%) as high, and 25 students (18.94%) as low. Female students had a higher mean logit score (0.60) than male students (-0.16), while no linear pattern of nomophobia was found across age groups. Among the four dimensions, not being able to communicate had the highest Mean Item Score (3.33), followed by not being able to access information (3.31), giving up convenience (3.28), and losing connectedness (2.80). These findings indicate that nomophobia is a relevant condition among students and may serve as empirical information for needs assessment and the development of student-centered guidance and counseling services.